Big things come in small packages. Biomass contribution of the krill Thysanoessa macrura to the marine ecosystem in the Kerguelen Plateau region - Jake Wallis; So Kawaguchi; Matsuno, K; Kerrie Swadling (2019)
Southern Ocean krill ( Thysanoessa macrura ) are a small and abundant species of krill in the Southern Ocean. It is considered the second most abundant krill species, with Antarctic krill ( Euphausia superba ) the biomass dominant species in Antarctic waters (Makarov, 1979; Hosie, 1991; Nordhausen, 1992). Euphausia superba is generally found south of the Polar Front, while T. macrura has a range that extends from the Antarctic coast to north of the sub-Antarctic front (Kirkwood, 1982; Cuzin-Roudy, et al. 2014). Consequently, T. macrura is likely the second most abundant euphausiid in the Antarctic, however estimates of its abundance in the Southern Ocean are largely lacking. Thysanoessa macrura play a vital role in the diet of many flying seabirds, fish and penguins. In the sub-Antarctic, the dietary contribution of T. macrura outweighs the contribution of other krill species and forms up to 80% of the diet of some sub-Antarctic bird species (Raymond et al., 2011).